The Egyptian Stock Market : Efficiency Tests and Volatility Effects - Mecagni, Mauro (IMF Working Papers; Working Paper ;, 1999)
The paper examines the behavior of stock returns in the Egyptian stock exchange, the efficiency of the market in pricing securities, and the relationship between returns and conditional volatility. GARCH(p,q)-M models estimated for the four best known daily indices indicate significant departures from the efficient market hypothesis; the tendency for returns to exhibit volatility clustering; and a significant positive link between risk and returns, which was significantly affected during the market downturn that followed the introduction of circuit breakers in the form of symmetric price limits on individual shares.